Effects of yoga on depressive symptoms in women with pregnancy: A systematic review and meta-analysis - Sasinun Punsuwun; Sarah Oerther; Chuntana Reangsing (Heliyon)
Background: While electroconvulsive therapy and antidepressants are standard treatments for depressed pregnant women, they are not without threats. The objective of this study was to quantitative synthesis of the literature regarding the effect of yoga interventions on depressive symptoms in pregnant women. Methods: Nine electronic databases were searched for primary studies with pregnant women with depression measured as outcomes and written in English. Based on the random-effects model, we used Hedges’ g to compute the effect size and examined the subgroup analysis. Results: We found twelve primary studies which included 738 participants who were 28.43 ± 1.92 years old across studies. The overall effect size using random-effects model was g = 1.120 (95%CI .52, 1.72, p < .001). Providing yoga to pregnant women with mood disorder had a lesser effect size (g = .10) than providing yoga to pregnant women without a mood disorder (g = 1.45). Funded studies had a lesser ES (g = .51) than those with unfunded (g = 1.98). Proving yoga in Eastern countries had a greater ES (g = 1.82) than providing yoga in Western (g = .40). No quality indicators showed moderator effects. Conclusion: When compared to controls, pregnant women who practiced yoga reported significantly improved depressive symptoms. Yoga might be an alternative complementary therapy that clinicians and other healthcare professionals might think about utilizing to help pregnant women who are depressed.